Correlations between physiological variables and performance in high level cross country off road cyclists. Issue 10 (23rd September 2005) - Impellizzeri, F M; Marcora, S M; Rampinini, E; Mognoni, P; Sassi, A
Abstract : Objectives: To examine the relations between maximal and submaximal indices of aerobic fitness and off road cycling performance in a homogeneous group of high level mountain bikers. Methods: 12 internationally competitive mountain bikers completed the study. Maximum oxygen uptake (V˙o 2max ), peak power output (PPO), power output (PO), and oxygen uptake (V˙o 2 ) at first (VT) and second (RCT) ventilatory thresholds were measured in the laboratory, and correlated with race time during a cross country circuit race. Results: The only physiological indices of aerobic fitness correlated with off road cycling performance were PO and V˙o 2 at RCT when normalised to body mass ( r  = −0.63 and r  = −0.66, respectively; p<0.05). VT, V˙o 2max, and PPO were not correlated to performance in this homogeneous group of high level mountain bikers. Conclusions: The results of this study suggest that submaximal indices of aerobic fitness such as PO and V˙o 2 at RCT are more important determinants of off road cycling performance than maximal indices such as PPO and V˙o 2max . This study confirms the importance of body mass for mountain biking performance. As aerobic fitness explained only 40% of the variance, other physiological and technical factors should be investigated, as they may be important determinants of cross country performance among elite mountain bikers.